Enhancement of DC Electrical Conductivity of Polypyrrole/Cu Nanocomposites Synthesized via In-situ Chemical Polymerization: Peningkatan Konduktivitas Listrik DC Nanokomposit Polipirol/Cu yang Disintesis melalui Polimerisasi Kimia In-situ - Manal J. Khalifa (Academia Open, 2025)
General Background: Conducting polymers, such as polypyrrole (PPy), offer a unique blend of mechanical flexibility and electronic functionality, making them attractive for diverse technological applications. Specific Background: Incorporating metal nanoparticles into PPy has shown promise in enhancing its electrical properties, particularly DC conductivity. Knowledge Gap: However, a systematic understanding of how varying copper (Cu) nanoparticle concentrations affect charge transport mechanisms and activation energy in PPy/Cu nanocomposites remains limited. Aims: This study aims to synthesize PPy/Cu nanocomposites via in-situ chemical polymerization and evaluate their DC conductivity and activation energy across a temperature range of 293–433 K. Results: The addition of Cu significantly enhanced conductivity, from 1.7×10⁻⁷ S/cm (pure PPy) to 8.6×10⁻⁴ S/cm (10 wt.% Cu), and reduced activation energy from 0.045 eV to 0.023 eV, indicating improved charge transport. Novelty: The findings reveal a clear correlation between Cu concentration and the formation of efficient conduction pathways, supported by percolation theory and interfacial charge transfer dynamics. Implications: These results position PPy/Cu nanocomposites as promising materials for applications in energy storage, sensing, and electromagnetic shielding, where high conductivity and tunable electrical behavior are critical.Highlight : High Conductivity Gain: Conductivity increased by 10,000× with 10 wt.% Cu addition. Efficient Charge Transport: Activation energy dropped from 0.045 eV (pure) to 0.023 eV (10 wt.% Cu). Application Potential: Suitable for energy storage, sensors, and electromagnetic shielding Keywords : Polypyrrole, Copper Nanoparticles, Conductivity Enhancement, Nanocomposites, Activation Energy